Anatomical single bundle anterior cruciate ligament reconstruction using the hamstring tendon graft to restore knee function in patients with sport injury, falling trauma or road traffic accident - Abd-Elmotalb, Emad-El-Deen; Shiha, Anis; Mousa, Shazly; Hafez, Abd-El-Rahman; Fawaz, Ahmed; Ali, Mohamed; Elsayed, Moustafa (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The purpose of this study was to evaluate the effect of anatomic single bundle ACL reconstruction using the hamstring tendon to restore knee function in patients with anterior cruciate ligament (ACL) injury. This was a prospective study with 30 patients (3 women and 27 men, aged 20-40 years) who underwent the arthroscopic single bundle ACL reconstruction using semi-tendinosus and gracilis autograft fixed with an interference screw with anatomical femoral tunnel placement at the Orthopaedic Surgery Department of Sohag University Hospital. All patients were followed up at 2 weeks, 6 weeks, 3 months and 6 months to assess their progress in the rehabilitation program and to address any complications. They were examined preoperatively for knee stability and associated injuries (i.e., meniscal injury), knee X-ray and MRI. All patients were assessed using the Lysholm score, the IKDC score, the Lachman score, and the pivot shift score preoperatively and six months postoperatively, and the results were compared. For data analysis, we used the Statistical Program for the Social Sciences (SPSS). Our study showed highly statistically significant differences between the preoperative and postoperative Lysholm scores, the IKDC score, the Lachman score, and the pivot shift score in favor of the postoperative scores (p < 0.001**). Anatomic single bundle ACL reconstruction using the hamstring tendon is an effective technique for restoring knee function and in patients with deficient ACL.